The Role of Bhabinkamtibmas in Preventing the Spread of Radicalism in the Ciomas Police Station Jurisdiction - Prabawa, Mukti (Advances in Police Science Research Journal, 2024)
The understanding of radicalism in Bogor is a phenomenon that still occurs, so it is the background in this study. There are some people among them who agree with the Islamic Khilafah. In addition, there are Islamic boarding schools which were closed due to radicalism. Ciomas Sub-District became one of the locations visited by MUI in the context of refuting radicalism. The prevention of the understanding of radicalism has been carried out by Bhabinkamtibmas, but there is still a radical understanding that can disturb the security and public order. So in this study the authors are interested in describing the development of radicalism, identifying the factors that influence Bhabinkamtibmas to prevent the development of radicalism, and analyzing the role of Bhabinkamtibmas to prevent the development of radicalism. In analyzing, the writer uses theories and concepts, including role theory, communication theory, management theory, concept of Bhabinkamtibmas, concept of radicalism, and concept of structural functionalism. By using a qualitative approach that is descriptive analytic, provides descriptive data in the form of words orally delivered by the primary source at the time of the interview, thus explaining the problem in depth. The results of the study found that: (1) the development of radicalism in suspected groups of terrorists, female students married to former Syria soldiers, and radical Social Organizations; (2) influencing factors include human resources, budget, facilities and infrastructure, the Bhabinkamtibmas method, community participation, cooperation and coordination and social communication; (3) the role of Bhabinkamtibmas to prevent the development of radicalism is still participatory. From the results of the study the authors suggest to Bhabinkamtibmas to use brochures in delivering kamtibmas messages. As for the advice to the Kasat Binmas to hold Bhabinkamtibmas capability training such as mass psychology and social communication, so that the leader’s policies are adjusted to operational support, and procurement of two-wheeled motor vehicles.